Verification of Qianlong Shutong Formula in the Treatment of Benign Prostatic Hyperplasia - Zhang, Ze-chao; Zhu, Min; Huang, Shu-ping; Wei, Zhi-feng; Chen, Yu; Shang, Chang-jie (Combinatorial Chemistry & High Throughput Screening, 2025)
AimsTo investigate the mechanisms through which Qianlong Shutong Formula (QLSTF) exerts its effects on the management of benign prostatic hyperplasia (BPH).Background: BPH is a prevalent condition among older men and poses significant management challenges due to the limited effectiveness and potential side effects associated with current treatment options. QLSTF, a traditional Chinese medicine, has been utilized in the treatment of BPH; however, its mechanism of action remains inadequately understood.ObjectiveThis study aimed to identify potential therapeutic targets of QLSTF for the management of BPH through the application of network pharmacology and subsequent experimental validation.MethodsQLSTF compounds were identified utilizing liquid chromatography-mass spectrometry (LC-MS). Potential targets of QLSTF, as well as BPH-related targets, were retrieved from public databases. Crucial bioactive ingredients, potential targets, and signaling pathways were acquired through bioinformatics analysis, including protein-protein interaction (PPI), as well as the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Subsequently, molecular docking was carried out to predict the combination of active compounds with core targets. Lastly, in vitro and in vivo experiments were conducted to further verify the findings.ResultsA total of 52 bioactive ingredients of QLSTF and 760 QLSTF-BPH-related targets were screened. Bioinformatics analysis revealed that Afzelin, Ononin, Glycitin, Emodin and Erythritol may be potential candidate agents. AKT1, SRC, STAT3, GRB2, HRAS, MAPK3, PIK3CA, PIK3R1, HSP90AA1, and EP300 could become potential therapeutic targets. PI3K-AKT signaling pathway might play an important role in QLSTF against BPH. Moreover, molecular docking suggested that Afzelin, Ononin, Glycitin, Emodin, and Erythritol combined well with AKT1, SRC, STAT3, HRAS, MAPK3, PIK3CA, and PIK3R1, respectively. In vitro and in vivo experiments showed that QLSTF could inhibit the proliferation of cells, as well as the PI3K-Akt signaling pathway, which further confirmed the prediction by network pharmacology strategy and molecular docking.ConclusionsQLSTF may exert its therapeutic effects on BPH by modulating the PI3K/AKT signaling pathway and inhibiting glandular hyperplasia. This study offers valuable insights into the therapeutic targets of QLSTF in the management of BPH.
Keywords: experimental verification